Opportunity meets uncertainty. Towards sustainable business in the Arctic region - Hirvonen, Tuuli (fi=Turun yliopisto. Turun kauppakorkeakoulu|en=University of Turku. Turku School of Economics|, 2016)
The Arctic region is experiencing a significant change in terms of climate change and a growing economic interest towards its natural resources and emerging business opportunities. The purpose of this study is to explore how can Finnish companies create sustainable business in the Arctic. This is done by examining the arctic business environment, identifying sectors with growth potential, addressing challenges related to operating in the Arctic and suggesting how to ensure sustainability and succeed in the globally competed arctic market. The theoretical framework is based on theories of sustainable development, corporate social responsibility and the role of strategy in creating sustainable business. Empirical data was collected by using qualitative research methods: first, background knowledge was formed based on written documents and, secondly, six expert interviews were conducted in early 2014. The interviewees represented the viewpoints of companies, political decision makers and NGO’s. The analysis of the data was conducted using thematic categorization. The empirical findings of the study suggest that in order to create sustainable business in the Arctic companies should adopt a long-term perspective, embrace a holistic approach to sustainability, understand interdependencies between the dimensions of sustainability and aim at high-level engagement in responsible behavior. To succeed in the arctic market core competencies, customer needs, multivendor cooperation and long-term presence need to be invested in on a company level. In addition, to promote and advance arctic development on a national level support is needed in terms of investments in infrastructure, funding research and design, creating a regulative framework and removing barriers of trade.